Tradução do self-care of diabetes inventory (SCODI) para o idioma português: instrumento para avaliação do autocuidado na diabetes - Brenna, Sílvia (2019)
Introduction: iabetes is one of the chronic non-communicable diseases, considered by the World Health Organization to be serious. I try to bear in mind the physical, emotional and social consequences, which in a way can drastically affect the individual's quality of life. In parallel with the increase in life expectancy, there was an epidemiological transition in emerging diseases: from a situation in which infectious diseases were prevalent, we evolved into a preponderance of chronic non-communicable diseases, both in developing and developed countries, it is expected that the number of elderly people with noncommunicable diseases will increase in proportion to the growth of the population, with a higher percentage exactly in the older age groups. Objectives: to evidence scientific production on the instruments for the assessment of self-care for diabetes used in Brazil and to translate the Self Care of Diabetes Inventory from Italian to Portuguese. Method: This is a methodological study, whose proposal was the translation process of the instrument - Self-Care Of Diabetes Index, an instrument that is based on a medium-range theory that consists of four parts for a total of 40 questions, evaluating healthy eating, physical exercise, monitoring, adherence to treatment, ability to solve problems, coping ability, and ability to monitor and prevent complications in adults with Type 1 and 2 Diabetes Mellitus. The study was conducted in João Pessoa / Paraíba / Brazil, at the Federal University of Paraíba and the translations were in collaboration with the Department of Science and Health at the Università degli Studi of Milan - Bicocca in Italy, in collaboration with the University of Pennsylvania in the United States of America. It was developed in the following stages: integrative review with the objective of evidencing the production of scientific knowledge about the adapted and validated instruments related to self-care in diabetes in the international reality and in Brazil; then the instrument translation process; after all, the elaboration of the final product, that is, the final Brazilian Portuguese translation of the Self-Care Of Diabetes Index. Results and Discussion: The translation of the instrument went through five stages, together with the questionnaire of psychometric data, based on the original version in Italian. The final instrument is available on the Self Care Measures website, linked to the University of Pennsylvania project in the United States of America. Conclusion: It is expected that the final product of this study, the translated instrument can contribute positively in the field of Nursing and Brazilian Gerontology, allowing the elderly to be more aware of their own chronic disease, and to be clear about possible complications, their methods of coping. and a full internalization of the importance of life habits, in addition to their necessary changes. Finally, it is hoped that this instrument can be a common language base in the assessment of self-care in diabetes, and that it be at national and international level.